Knowledge Management System in a Competitive Business - Kubiak, Bernard F. (Advanced Information Technologies for Management – AITM 2008, 2008)
The article discusses how the knowledge management system (KMS) influences the implementation of organisation's objectives and strategy and how it increases its effectiveness and competitive edge. The process of building KMS has been presented together with intelligent tools supporting these activities. The article emphasises the significance of predefining information-related needs of all management levels and the informational contents of reports with the application of Business Objects in order to design the data and document warehouse adequately. The structure and the processes taking place there have been discussed in terms of servicing organisation's business and information processes.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 105-115